2001
DOI: 10.1007/bf02490417
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on analyte losses in systems suited for large-volume on-column injections

Abstract: Use o~ a large-volume injection system with a solvent vapour exit (SVE) requires optimisation. An appropriate strategy is to determine the evaporation rate by increasing the injection time at a fixed injection speed, injection temperature and head pressure. When measuring the flow rate in the carrier gas supply line to the on-column injector, optimisation can be very rapid: some five injections of pure solvent will be sufficient.When working under pa~ially concurrent solveni evaporation conditions, loss of vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In analysis of L-WS using direct liquid injection at high temperature, a combination of a direct injection (DI) liner and program temperature vaporizing can provide high sample transfer efficiencies to the GC column to decrease sample losses (Ouyang et al, 2005). To facilitate LVI and limit sample loss (e.g., loss of volatiles), modifications to the injection system is required; e.g., by applying partially concurrent solvent evaporation process (PCSE) combined with an on-column injector and a retention gap (e.g., deactivated fused silica) (Adahchour et al, 2001). …”
Section: Figure 2 Comparison Of the Mean Rf Values Of Each Compound mentioning
confidence: 99%
“…In analysis of L-WS using direct liquid injection at high temperature, a combination of a direct injection (DI) liner and program temperature vaporizing can provide high sample transfer efficiencies to the GC column to decrease sample losses (Ouyang et al, 2005). To facilitate LVI and limit sample loss (e.g., loss of volatiles), modifications to the injection system is required; e.g., by applying partially concurrent solvent evaporation process (PCSE) combined with an on-column injector and a retention gap (e.g., deactivated fused silica) (Adahchour et al, 2001). …”
Section: Figure 2 Comparison Of the Mean Rf Values Of Each Compound mentioning
confidence: 99%
“…Although a pre-column of 3 m is generally used, a number of studies have shown that it really acts as a restricting pre-column, eliminating the precolumn can increase the carrier gas flow through the retention gap thus increasing the evaporative rate. 26,47 The COC provides no separation of analytes from co-injected matrix components 17 and COC inlets thus have the lowest tolerance to coinjected matrix components followed by pulsed splitless or splitless mode. The PTV with solvent split technique has the highest tolerance for matrix components.…”
Section: Cold On-column (Coc) Injectionmentioning
confidence: 99%
“…As no single analytical method is able to identify all detected substances at the moment [13][14][15], especially in complex matrices like recycled plastics, an optimization of current testing schemes is urgently needed. As the physico-chemical properties of genotoxins regarding their hydrophobicity and volatility can be quite diverse [16], a combination of analytical methods is necessary to detect a broad spectrum of possible DNA-reactive, mutagenic substances. That said, even such a combination will not result in a complete identification, as analytical reference standards are not yet available for all compounds, especially for as yet unknown NIASs [17].…”
Section: Introductionmentioning
confidence: 99%